Analisis Penggunaan Data Sosial Media Untuk Penelitian: Studi Etika Dan Regulasi Informatika - Sani Shalihamidiq; Nana Mulyana Maghfur; Rahmat Alfanza; Didi Juardi (Peneliti.net, 2022)
Public data contained on social media is widely used by researchers, the data can be in the form of text, photos, videos to locations and hashtags created by social media users themselves. Many researchers use social media as a place to find data for free because the data is already public. However, ethically the use of data violates existing rules, because many social media users do not know that their data is used as research material. In this article, the author aims to analyze the ethics of researchers in using data sourced from public social media, as well as regulatory provisions regulated by the government and service providers on the use of data.